Serum Homocysteine Level Is Positively Correlated With Serum Uric Acid Level in U.S. Adolescents: A Cross Sectional Study - Shi, Yumeng; Wu, Zuxiang; Wu, Ji; Chen, Zhiqiang; Li, Ping (Frontiers in Nutrition, 2022)
Background: Physiologically, the levels of homocysteine (Hcy) and serum uric acid (SUA) are closely related; however, clinical studies on the relationship between Hcy and SUA have drawn different conclusions and have not analyzed this association among adolescents. This study therefore aimed to evaluate the relationship between Hcy and SUA levels among adolescents. Methods: In this study, we performed a cross-sectional analysis of data from the National Health and Nutrition Examination Survey for the period 1999-2006, which included 5,404 adolescents aged 12-19 years. An elevated SUA level was defined as ≥5.5 mg/dL. Multivariate logistic regression and multivariate linear regression models were also applied in this study. Results: The mean concentrations of Hcy and SUA were 6.0 μmol/L and 5.0 mg/dL, respectively, and 33.6% of the participants had SUA levels of ≥5.5 mg/dL. There was a dose–response relationship between Hcy and SUA, and Hcy was linearly positively correlated with SUA. The β value (95% confidence interval [CI]) for SUA in the fully adjusted model was1.43 (95% CI: 1.18, 1.68). The multivariate logistic regression model showed that per 1 increment in log-transformed Hcy, the risk of elevated SUA levels increased by 8.80 times (odds ratio, 8.80, 95% CI: 4.25, 18.20). Subgroup analyses showed that the relationship between Hcy and SUA was significantly different according to sex, age, body mass index (BMI), and estimated glomerular filtration rate (eGFR) stratification (P for interaction <0.05). Conclusion: Hcy levels were positively correlated with SUA levels and elevated SUA levels among U.S. teenagers, and this effect was more significant among boys aged ≥17 years and among people with lower BMI and eGFR.